2018
DOI: 10.3390/ijms19092551
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Neurochemistry of the Porcine Ileocaecal Valve Projecting Sensory Neurons in the Dorsal Root Ganglia and the Influence of Lipopolysaccharide from Different Serotypes of Salmonella spp. on the Chemical Coding of DRG Neurons in the Cell Cultures

Abstract: The ileocecal valve (ICV)—a sphincter muscle between small and large intestine—plays important roles in the physiology of the gastrointestinal (GI) tract, but many aspects connected with the innervation of the ICV remain unknown. Thus, the aim of this study was to investigate the localization and neurochemical characterization of neurons located in the dorsal root ganglia and supplying the ICV of the domestic pig. The results have shown that such neurons mainly located in the dorsal root ganglia (DRG) of thora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 83 publications
1
8
0
Order By: Relevance
“…Our previous in vitro observations confirmed that LPS shows differences in activity to SP and GAL even within particular serotypes of Salmonella spp. [ 53 ]. Therefore, considerations of different LPS biological activity depending on various bacterial sources and long-term consequences of LPS different doses must be considered in a research strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous in vitro observations confirmed that LPS shows differences in activity to SP and GAL even within particular serotypes of Salmonella spp. [ 53 ]. Therefore, considerations of different LPS biological activity depending on various bacterial sources and long-term consequences of LPS different doses must be considered in a research strategy.…”
Section: Discussionmentioning
confidence: 99%
“…To date, preclinical CFS studies mainly used LPS-, poly I:C-, or chronic stress-induced animal models [18,28]. For LPS model, we used LPS originated from Escherichia coli (O111:B4), which is known to induce the illness-like symptoms [29,30]. The LPS dose (3 mg/kg) and time duration (24 h after injection) were chosen based on the concerns about non-response versus septic shock [31,32] and peak time of locomotor impairment [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that LPS is not homogeneous [170]. Additionally, studies have found that structural and chain length differences in LPS between serotypes of Salmonella are sufficient to drive different host immune responses [171][172][173]. S. Typhimurium uses PbgA and PmrA/Pmrb system to influence LPS assembly and drive variable host Type I IFN responses for their survival in various ecological niches [157,[173][174][175].…”
Section: Escape Of Innate Immune Systemmentioning
confidence: 99%